Study of changes in the aging process, microstructure, and mechanical properties of AA2024–AA1050 nanocomposites created by the accumulative roll bonding process, with the addition of 0.005 vol.% of alumina nanoparticles - Hamed Roghani; Ehsan Borhani; Ehsan Ahmadi; Hamid Reza Jafarian (Discover Nano, 2024)
Abstract We created AA2024–AA1050 and AA2024–AA1050/0.005 vol.% Al2O3 nanocomposites by six accumulative roll bonding (ARB) process cycles. We used AA2024 and AA1050 sheets with a thickness of 0.7 mm and plate-shaped alumina nanoparticles to create a composite. The two AA1050 and one AA2024 sheets (among the two AA1050 sheets) were ARB-ed up to six cycles with and without adding alumina nanoparticles. Also, a sample of the AA1050 without composite making was ARB-ed up to six cycles. We aged some composites after the ARB process in the furnace at 110, 150, and 190 °C. This project performed SEM, TEM, and EDS-MAP analyses, tensile strength, microhardness, and Pin-on-Disc tests to study the ARB-ed sheets. The results of the tensile tests showed that the tensile strength of AA2024–AA1050 created by the six cycles ARB process was two times more than primary AA1050. Also, the wear resistance of this composite was 74% more than six cycles ARB-ed the AA1050. Using 0.005 vol.% alumina nanoparticles in AA2024–AA1050 composite improved its wear resistance by 30%. In the following, the aging process caused an improvement in tensile strength and total elongation of AA2024–AA1050/Al2O3 nanocomposites.